2019
DOI: 10.1002/oby.22609
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Waist Circumference and Dementia in Older Persons: A Nationwide Population‐Based Study

Abstract: Objective This study examined whether a positive association exists between waist circumference (WC) and dementia among older persons. Methods The study population comprised 872,082 participants aged 65 years and older who participated in a Korean national health screening examination between January 1, 2009, and December 31, 2009. Adjusted hazard ratios and 95% CIs for dementia during follow‐up from 2009 to 2015 were calculated according to baseline BMI and WC categories. Results After a multivariate adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
(41 reference statements)
2
19
1
Order By: Relevance
“…These findings are consistent with previous reports that separately analysed the relationship of cognitive function with muscle strength or waist circumference [ 6 , 8 , 12 , 36 ]. One study in Taiwan found that low muscle strength and low physical performance were more associated with global cognitive function impairment, compared to sarcopenia [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous reports that separately analysed the relationship of cognitive function with muscle strength or waist circumference [ 6 , 8 , 12 , 36 ]. One study in Taiwan found that low muscle strength and low physical performance were more associated with global cognitive function impairment, compared to sarcopenia [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…A longitudinal study demonstrated that poor muscle function is a better predictor of incidence MCI and cognitive decline, compared to reduced lean muscle mass [ 6 ]. On the other hand, it has been reported that despite normal BMI, high waist circumference increases the risk of developing dementia in older people [ 12 ]. Additionally, central fat mass was associated with MCI, but skeletal muscle mass was not [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, participants with an abnormally large waist circumference were at 1.8 times greater risk for poor cognitive function. In addition, a large-scale cohort study involving 872,082 adults aged 65 years or older reported that abdominal obesity, as measured by waist circumference, significantly increased the risk of dementia ( Cho et al, 2019 ). However, contradictory findings have also been reported, showing an association between lower abdominal fat mass and worse cognitive function in elderly women ( Bagger et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, individuals of shorter height may have higher health risks than taller individuals in the moderately-to-large WC group for both sexes and across different ages among Japanese adults [26]. Furthermore, WC has also been associated with a significantly increased risk of dementia among older adults [27]. Additionally, abdominal obesity (WC > 88 cm) has also been positively associated with fragility fractures in a sample of community-dwelling elderly Israeli women [28].…”
Section: Plos Onementioning
confidence: 99%